Tingkat Kepercayaan Mahasiswa Fikom Untar pada Akurasi Berita Covid-19 di Kompas.com - Gherry Daniel; Sinta Paramita; Doddy Salman (Kiwari, 2022)
News of Covid-19 is published in many cyber media portals. The issue of Covid-19 is an issue that is currently hot in all parts of the earth. This of course makes Kompas.com as a cyber news media to present news about the Covid-19 issue. This study aims to find out how the level of trust of FIKOM UNTAR students in reading and acting on cyber news about the Covid-19 issue on the cyber media Kompas.com, the worst covid case in Indonesia in July. This study uses the theory of digital journalism, which makes the media can be used as a source of information in the form of audio and visual. This study uses quantitative research methods, researchers took 100 samples from the student population of FIKOM UNTAR. The sampling technique was carried out by distributing questionnaires to the 2018 - 2020 FIKOM UNTAR students. This study obtained the results of the effect of information accuracy on the 50.5 percent confidence level. And the results of the T test are known that Ho is rejected and Ha is accepted which means that there is an influence between the variables x and y. Berita Covid-19 dimuat di banyak portal media siber, Isu tentang Covid-19 merupakan isu yang sedang panas panasnya di seluruh bagian bumi. Hal ini tentu saja membuat Kompas.com sebagai media berita siber menyajikan berita tentang isu Covid-19. Penelitian ini bertujuan mengetahui bagaimana tingkat kepercayaan Mahasiswa Fikom UNTAR dalam membaca dan bersikap pada berita siber tentang isu Covid-19 di media siber Kompas.com, kasus covid terburuk di Indonesia di bulan Juli. Penelitian ini menggunakan teori jurnalisme digital, yang membuat media dapat digunakan menjadi sebuah sumber informasi yang bentuknya bisa berupa audio dan visual.  Penelitian ini menggunakan metode penelitian kuantitatif, peneliti mengambil 100 sampel dari populasi Mahasiswa Fikom UNTAR. Teknik pengambilan sampel dilakukan dengan menyebarkan kuesioner kepada Mahasiswa FIKOM UNTAR angkatan 2018 – 2020. Penelitian ini mendapatkan hasil pengaruh akurasi informasi terhadap tingkat kepercayaan 50,5 persen.  Dan hasil uji T diketahui bahwa Ho ditolak dan Ha diterima yang berarti bahwa adanya pengaruh antara variabel x dan y.